A pratical submaximal test to predict maximal running performance in the heat - Lambert, M.; Mann, T. N.; Marino, F. E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The aim was to predict running performance in the heat from changes in heart rate, rectal temperature and perceived exertion during submaximal running in cooler conditions. Methods Twelve highly trained male distance runners were recruited for the study (24.2±3.5 yrs). Subjects were tested on 3 separate days with a 30 min submaximal test followed by a 5 min rest and then a maximal self-paced 8 km time trial. The tests were randomised in either cool (15°C), moderate (25°C) or hot (35°C) conditions. Results Heart rate (HR) at the end of the submaximal trial during 15°C (154±10 b/min) was significantly less than HR at the end of 25° C (161±9 b/min) and 35° C (176±13 b/min).